2012
DOI: 10.1371/journal.pone.0029653
|View full text |Cite
|
Sign up to set email alerts
|

Expression Signature of IFN/STAT1 Signaling Genes Predicts Poor Survival Outcome in Glioblastoma Multiforme in a Subtype-Specific Manner

Abstract: Previous reports have implicated an induction of genes in IFN/STAT1 (Interferon/STAT1) signaling in radiation resistant and prosurvival tumor phenotypes in a number of cancer cell lines, and we have hypothesized that upregulation of these genes may be predictive of poor survival outcome and/or treatment response in Glioblastoma Multiforme (GBM) patients. We have developed a list of 8 genes related to IFN/STAT1 that we hypothesize to be predictive of poor survival in GBM patients. Our working hypothesis that ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 21 publications
(35 reference statements)
6
92
1
1
Order By: Relevance
“…Previous studies showed that Stat1 mediates the expression of a set of IFNinducible genes known as IFN-related DNA damage-resistance signature, which renders different tumor types increasingly resistant to chemotherapy and radiation therapies (62)(63)(64)(65). More recent work demonstrated that unphosphorylated Stat1 mediates the induction of genes that protect cells from virus infection or DNA damage in response to prolonged treatment with IFN-β (2).…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 99%
“…Previous studies showed that Stat1 mediates the expression of a set of IFNinducible genes known as IFN-related DNA damage-resistance signature, which renders different tumor types increasingly resistant to chemotherapy and radiation therapies (62)(63)(64)(65). More recent work demonstrated that unphosphorylated Stat1 mediates the induction of genes that protect cells from virus infection or DNA damage in response to prolonged treatment with IFN-β (2).…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 99%
“…In addition, the response of GBM tumors to radiation predicts the patient lifespan after treatment. In this regard, we described elsewhere that ISG expression correlated with poor overall survival in patients with GBM (15). To investigate whether LGP2 gene expression is also related to clinical outcomes in patients with GBM, we analyzed two independent GBM datasets from the Cancer Genome Atlas (CGA; http://cancergenome.nih.gov/) (n = 382) and the Phillips et al study (n = 77) (37).…”
Section: Ir Induces Cytotoxic Type I Ifnmentioning
confidence: 99%
“…Many of these constitutively expressed ISGs have been characterized as antiviral genes (11). Recently, enhanced levels of constitutively expressed ISGs have been reported in advanced cancers and were often associated with a poor prognosis related to aggressive tumor growth, metastatic spread, resistance to IR/chemotherapy, or combinations of these factors (11)(12)(13)(14)(15)(16)(17)(18). The studies presented in this report are based on the hypothesis that a specific set of constitutively expressed ISGs, whose enhanced expression is by cytotoxic stress, confers a selective advantage to individual tumor clones (5,9,10,13,19).…”
mentioning
confidence: 99%
“…Authors of that report hypothesized that the poor prognosis could be attributable to the chemoresistance and/or radiation resistance of tumors that express STAT-1. 10 Work on other tumors and cell lines has shown that, like IGFBP-3, STAT-1 also has a dual role in cancer. For example, the overexpression of STAT-1 has been associated with a better outcome in squamous cell carcinoma and mammary cancers.…”
mentioning
confidence: 99%
“…Another study points toward a protumorigenic role of STAT-1 in GBM. 10 These contradictory reports of STAT-1 in GBM make it an interesting molecule for further detailed analysis.…”
mentioning
confidence: 99%